Valuating element sign modification of the meaning of some words of the German language in the period of Nazi Diktatorship in Germany - T V Savina (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2011)
The reasons of valuating element sign modification of some words are often out of the laguage sphere. Sometimes under the influence of extralinguistic factors a neutral from the point of viev of valuation word can gain a valuating seme and a valuating word can change a valuating sign to the opposite one (from «+» to «-» and vice-versa). Such events took place in the German language in the period of Nazi dictatorchip as well (from 1933 to 1945). The present article is conserned with the research of the reasons and pecualiarities of valuating sign modification of some words of the German language in the given historical epoch.